Supervising the Performance of Teachers in Bulawayo Metropolitan Province - Ngwenya, Victor Chaboneka; Ngwenya, Obert (Journal of Research in Marketing (ISSN: 2292-9355), 2017)
The purpose of this study was to investigate the appropriate models Education Managers could use to enhance the performance of teachers in the teaching and learning process through supervision in Bulawayo Central District. The epistemological foundations informing this study was a post-positivist paradigm employing a quantitative approach. Structured questionnaires were used to gather data from the respondents (N=50) who were randomly selected from the ten schools. The major finding was that both Education Managers and teachers investigated were pedagogical qualified. Weighing in were their experience and maturation levels. Similarly, the emphasis on measurable standards, getting inputs from the teachers before writing a report, successful accomplishment of tasks and being both human and task oriented in practice demonstrated that a contingent approach was being employed by supervisors. In the process, models were integrated, although, the Clinical Supervision Model unconsciously. A need to staff develop the supervisory corps in the latter arose.